Pengaruh Akuntansi Zakat terhadap Akuntabilitas Publik : (Studi Kasus Di Badan Amil Zakat Nasional (BAZNAS) dan Lembaga Amil Zakat (LAZ) Kabupaten/Kota Provinsi Sumatera Selatan) - Taufiq, Taufiq; Meutia, Inten; Alkahfi, Bayu Dharmaraga (UPT Publikasi Ilmiah UNISBA, 2020)
The purpose of this study was to determine the effect of zakat accounting on public accountability of BAZNAS and LAZ in South Sumatra Province with the methodology used was descriptive using a questionnaire. While the data analysis used is simple linear regression analysis. So from this study it can be seen that the accounting for zakat influences the accountability of BAZNAS and LAZ in South Sumatra Province by 73.9%, then based on the results of the study it is known that the tendency of zakat accounting carried out by zakat institutions in South Sumatra Province has unfavorable criteria of 3 institutions or 10%, 2 institutions are quite good criteria, 5 institutions with good criteria and with very good criteria are 66.6% or as many as 20 amil zakat institutions.